Identifying Blind Spot Zone for Passenger Cars using Grid-Based Technique - Hashim, M.S.M.; Ismail, A.H.; Abu Bakar, S.; Muhamad Azmi, M.S.; Mohamad Razlan, Z.; Harun, A.; Kamarrudin, N.S.; Ibrahim, I.; Faizi, M.K.; Saad, M.A.M.; Rani, M.F.H.; Mahayadin, A.R.; et al. (Journal of the Society of Automotive Engineers Malaysia, 2021)
A person driving a passenger car depends on the rear view mirror and two side-mounted mirrors to observe the surrounding in order to see vehicles approaching from behind. However, the approaching vehicle may enter a region outside the driver’s field of view, making it inconspicuous to the driver. Such a region is known as the blind spot zone (BSZ). Although driving schools emphasize the importance of checking for vehicles in BSZ before attempting to change lane, many fatal collisions have occurred during lane changing. Thus, it is important to understand BSZ particularly its corresponding parameters in order to develop an effective system to detect approaching vehicles and provide warning to the driver. In this paper, a systematic approach using a grid-based technique is proposed to model the BSZ. An experiment was conducted using a commonly used passenger car in Malaysia as a test bed to model the BSZ. Controlled experimental parameters were introduced, and the final results showed that BSZ can be identified using the grid-based technique.